The Effectiveness of Healthy Lifestyle Education Combined with Yoga Therapy on Self-Care Behaviors and Daily Physical Activity Levels in Overweight Individuals at Risk of Developing Diabetes - Abdolkarimy Nazary, Maryam; Agahheris, Mojgan; Kordmirza Nikoozadeh, Ezzatolah; Rahmanian, Mahdieh; Abdolhoseini, Amir (KMAN Counseling & Psychology Nexus, 2026)
The present study aimed to examine the effectiveness of healthy lifestyle education combined with yoga therapy on self-care behaviors and daily physical activity levels in overweight individuals at risk of developing diabetes. This study was a quasi-experimental study with a pretest, posttest, and follow-up design with a control group. The statistical population consisted of overweight individuals at risk of developing diabetes. After meeting the inclusion criteria, participants were selected through purposive sampling and randomly assigned to the experimental and control groups. The experimental group received healthy lifestyle education combined with yoga therapy over 10 sessions, while the control group remained on the waiting list. Data were collected using the Diabetes Self-Care Questionnaire and daily physical activity indicators and were analyzed using repeated-measures analysis of variance. The results showed that healthy lifestyle education combined with yoga therapy had a significant effect on improving self-care behaviors and increasing daily physical activity levels in the experimental group compared with the control group (P < 0.05). These changes also persisted at the follow-up stage, indicating the stability of the intervention effects. The findings suggest that healthy lifestyle education combined with yoga therapy can improve self-care behaviors and daily physical activity levels in overweight individuals at risk of developing diabetes by enhancing health awareness, increasing individual responsibility, and encouraging regular physical activity. Therefore, the use of this intervention is recommended as a complementary strategy in diabetes prevention programs.